Vulnerabilidade de adolescentes à gestação: estudo desenvolvido em uma UBS de um município paulista - Magalini, Teresa Cristina (2015)
It is estimated that, in Brazil, a million teenage girls give birth each year, which represents 20% of the total number of live births. Adolescence is a phase marked by rapid physical and emotional changes that may make it more vulnerable to healthrelated aspects, being the pregnancy a risk reason for the occurrence of health problems for both the teenager as to their concepts.In an attempt to understand this process and get subsidies for a better performance of nursing in public health was developed this study aiming to identify the factors related to vulnerability to pregnancy in adolescents.This is a descriptive study which have as sample teenagers who seek basic health unit in a paulista municipality in order to perform the test for confirmation of pregnancy and that the test results be positive. The data were collected through the questionnaires and subsequently analyzed by using descriptive statistics.Of the 27 teenagers study, most participants (44,4%) were 16 years old, 92% were single and 51,8% had stopped studying, the predominant education level was high school 68%. Prevailed also the low educational level of mothers (81,4%). Most live in homes with an income of 1 to 2 basic salaries, belonging to economic class C1. In relation to sexual life menarche happened to 12 years teenagers preferably (33,3%) and the beginning of sexual life at the age of 13 and 14 years (29,6%). Most reports receive sexual education from the school and mother (33,3%). The methods of birth control are quite known but 20,6%of the teens reports do not use them so the pregnancy happened mainly because they thought it wouldn't happen to them (35,2%) or for not having prevented (29,4%). Regarding the vulnerability, we can infer that the social dimension is the most frequent, as it relates to the material, cultural and political aspects which relate to social life, such as region of residence for the teens of this study.